Time and Flesh: Exploring the Embodied Experiences of Black Mothers - Tucker, Amber (Violence against women, 2025)
Drawing on Black feminist theories of intersectionality and concepts of temporality and embodiment, this study centers Black girlhood to understand Black girls embodied journeys of “becoming” Black women. Findings revealed that: (a) Black girls often have complicated histories that lead to constrained and liberatory choices in adulthood and motherhood; (b) becoming a Black woman involves continual adaptations to temporal and historical contexts; and (c) Black motherhood is a contested space, deeply shaped by remembering Black girlhood and navigating maternal responses to legacies of harm. This study highlights the challenges and strengths in the transitory states of Black womanhood.